Illumina Sequencing Approach to Characterize Thiamine Metabolism Related Bacteria and the Impacts of Thiamine Supplementation on Ruminal Microbiota in Dairy Cows Fed High-Grain Diets - Pan, Xiaohua; Xue, Fuguang; Nan, Xuemei; Tang, Zhiwen; Wang, Kun; Beckers, Yves; Jiang, Linshu; Xiong, Benhai (Frontiers in Microbiology, 2017)
The requirements of thiamine in adult ruminants are mainly met by ruminal bacterial synthesis, and thiamine deficiencies will occur when dairy cows overfed with high grain diet. However, there is limited knowledge with regard to the ruminal thiamine synthesis bacteria, and whether thiamine deficiency is related to the altered bacterial community by high grain diet is still unclear. To explore thiamine synthesis bacteria and the response of ruminal microbiota to high grain feeding and thiamine supplementation, six rumen-cannulated Holstein cows were randomly assigned into a replicated 3×3 Latin square design trial. Three treatments were control diet (CON, 20% dietary starch, DM basis), high grain diet (HG, 33.2% dietary starch, DM basis) and high grain diet supplemented with 180 mg thiamine/kg DMI (HG+T). On day 21 of each period, rumen content samples were collected at 3 h postfeeding. Ruminal thiamine concentration was detected by high performance liquid chromatography. The microbiota composition was determined using Illumina MiSeq sequencing of 16S rRNA gene. Cows receiving thiamine supplementation had greater ruminal pH value, acetate and thiamine content in the rumen. Principal coordinate analysis and similarity analysis indicated that HG feeding and thiamine supplementation caused a strong shift in bacterial composition and structure in the rumen. At the genus level, compared with CON group, the relative abundances of 19 genera were significantly changed by HG feeding. Thiamine supplementation increased the abundance of cellulolytic bacteria including Bacteroides, Ruminococcus 1, Pyramidobacter, Succinivibrio and Ruminobacter, and their increases enhanced the fiber degradation and ruminal acetate production in HG+T group. Christensenellaceae R7, Lachnospira, Succiniclasticum, and Ruminococcaceae NK4A214 exhibited a negative response to thiamine supplementation. Moreover, correlation analysis revealed that ruminal thiamine concentration was positively correlated with Bacteroides, Ruminococcus 1, Ruminobacter, Pyramidobacter and Fibrobacter. Taken together, we concluded that Bacteroides, Ruminococcus 1, Ruminobacter, Pyramidobacter and Fibrobacter in rumen content may be associated with thiamine synthesis or thiamine is required for their growth and metabolism. In addition, thiamine supplementation can potentially improve rumen function, as indicated by greater numbers of cellulolytic bacteria within the rumen. These findings facilitate understanding of bacterial thiamine synthesis within rumen and thiamine’s function in dairy cows.